2019
DOI: 10.1037/xge0000578
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive basis for the split-attention effect.

Abstract: We would like to express our gratitude to Alex van Straaten, Sven Cammeraat, and Tudor Cristea for their help during the data collection. We would also like to thank prof. dr. Rolf Plötzner for providing the materials used in Experiment 3. This research was funded by the Excellence Initiative grant from the Erasmus University Rotterdam awarded to the Educational Psychology section. We also thank the Erasmus Behavioral Lab, especially Marcel Boom, for their continued help in the lab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 64 publications
1
31
1
Order By: Relevance
“…While these studies did not use typical multimedia learning tasks, a few studies exist in multimedia learning research which corroborate these findings using more educationally relevant materials (Bauhoff, Huff, & Schwan, 2012;Huff, Bauhoff, & Schwan, 2010). Together, these studies indicate the importance of distance and its effect on cognitive load, and are in accordance with the results of Experiment 1 and 2 reported by Pouw et al, 2019. In learning from spatially separated information sources one possible strategy to support learning is to signal corresponding pieces of information in both information sources (cf. De Koning & Jarodzka, 2017;De Koning, Tabbers, Rikers, & Paas, 2009).…”
Section: The Influence Of Spatial Distance and Signaling On Cognitivesupporting
confidence: 90%
See 3 more Smart Citations
“…While these studies did not use typical multimedia learning tasks, a few studies exist in multimedia learning research which corroborate these findings using more educationally relevant materials (Bauhoff, Huff, & Schwan, 2012;Huff, Bauhoff, & Schwan, 2010). Together, these studies indicate the importance of distance and its effect on cognitive load, and are in accordance with the results of Experiment 1 and 2 reported by Pouw et al, 2019. In learning from spatially separated information sources one possible strategy to support learning is to signal corresponding pieces of information in both information sources (cf. De Koning & Jarodzka, 2017;De Koning, Tabbers, Rikers, & Paas, 2009).…”
Section: The Influence Of Spatial Distance and Signaling On Cognitivesupporting
confidence: 90%
“…In a recent study by Pouw et al, 2019 three experiments were conducted to investigate whether the split-attention effect is actually caused by the spatial separation of the information sources. In the first two experiments, participants had to judge the similarity of two spatially separated cards with symbols that could vary in form, number, and colour.…”
Section: The Influence Of Spatial Distance and Signaling On Cognitivementioning
confidence: 99%
See 2 more Smart Citations
“…In the field of learning from instructional visualisations for example, de Koning, Tabbers, Rikers, and Paas (2010) showed that attentional cues designed to guide attention to task-relevant information in the visualisation helped learners to focus their attention on the relevant content, but this did not lead to better learning outcomes on a subsequent test than when having studied the visualisation without attention-directing cues. Similarly, in the field of multimedia learning, Pouw, Rop, de Koning, and Paas (2019) observed less integrative eye movements during learning of text-picture instructions when the spatial distance between text and picture was increased even though learning outcomes remained similar in the large and small spatial-distance conditions. The results of this study demonstrate that such effects also exist when processing narrative text after having inspected a picture.…”
Section: Discussionmentioning
confidence: 85%